FIRST RECORDS OF Neosilba spp. (Diptera: Lonchaeidae) IN THE STATE OF MATO GROSSO, BRAZIL (Nativa, 2024)
Responsible for damage infesting fruits and flower buds, Diptera species of the family Lonchaeidae have caused concern to farmers throughout Brazil. Knowing the abundance of insects in the Amazon region and the scarcity of publications on the species that affect fruit trees in the state of Mato Grosso, this work to carry out a survey of the species associated with the Neosilba (Diptera: Lonchaeidae) in the state. Fruit collections were carried out in six municipalities, whose samples were taken to the Entomology Laboratory of the Federal University of Mato Grosso, where they were placed in plastic containers containing expanded vermiculite to accommodate the pupae. After the emergency, the insects were sacrificed and sent for identification. A total of 163 specimens belonging to four species of Neosilba were obtained, all reported for the first time in the state of Mato Grosso. Neosilba inesperata Strikis & Prado, 2009 is reported for the first time in the Brazilian Amazon. Several new associations between Neosilba species and host plants are made for the region.Keywords: Lance flies; Southern Amazon; distribution; Tephritoidea. Primeiros registros de Neosilba spp. (Diptera: Lonchaeidae) no estado de Mato Grosso, Brasil  RESUMO: Responsáveis por estragos em frutos e botões florais, espécies de dípteros da família Lonchaeidae tem causado preocupação a agricultores em todo o Brasil. Sabendo-se da abundância de insetos na região amazônica e da escassez de publicações sobre as espécies que afetam as frutíferas no estado de Mato Grosso, este trabalho visa realizar um levantamento das espécies associadas ao gênero Neosilba (Diptera: Lonchaeidae) no estado. Foram realizadas coletas de frutos em seis municípios, cujas amostras foram encaminhadas ao Laboratório de Entomologia da Universidade Federal de Mato Grosso, onde foram acondicionadas em recipientes plásticos contendo vermiculita expandida para acomodação das pupas. Após a emergência, os insetos foram sacrificados e enviados para identificação. Foram obtidos 163 espécimes pertencentes a quatro espécies de Neosilba, todas reportadas pela primeira vez no estado do Mato Grosso. Neosilba inesperata Strikis & Prado, 2009 é reportada pela primeira vez na Amazônia brasileira. Diversas novas associações entre espécies de Neosilba e plantas hospedeiras são realizadas para a região.Palavras-chave: Lonqueídeos; Amazônia meridional; distribuição; Tephritoidea.